Robert Ervin Howard’s Vision of the Supernatural in Beyond the Black River - GULANOWSKI, PIOTR (Journal of Education Culture and Society, 2020)
The plot and the presented world of Robert Ervin Howard’s Beyond the Black River are representative of sword and sorcery, a subgenre of fantasy fiction that Howard is claimed to have pioneered. It has been proposed that the worlds in fantasy fiction are coherently organised, natural, and material. Nevertheless, supernatural elements that are not consis-tent with the structure of the universe are present. The struggle between the structured worlds and the chaotic supernatural that is resolved by an intervention of a barbarian hero constitute the essence of the sword and sorcery subgenre. These elements can also be found in Beyond the Black River by Howard, who employs contrastive images to present the super-natural.